2015
DOI: 10.1038/jp.2015.120
|View full text |Cite
|
Sign up to set email alerts
|

Association between marijuana use and adverse obstetrical and neonatal outcomes

Abstract: Maternal marijuana use does not increase the risk of adverse obstetrical outcomes or fetal anomalies, but does increase the risk for small for gestational age and neonatal intensive care unit admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
91
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 15 publications
10
91
1
Order By: Relevance
“…After duplicates were removed, 6542 publications were screened by title and abstract. Of these, 109 were retrieved for full‐text review and 41 studies were included in our scoping review …”
Section: Resultsmentioning
confidence: 99%
“…After duplicates were removed, 6542 publications were screened by title and abstract. Of these, 109 were retrieved for full‐text review and 41 studies were included in our scoping review …”
Section: Resultsmentioning
confidence: 99%
“…The rates of NICU admission in our study are similar to those published by Warshak et al who identified an increased rate of NICU admission among women (N=6468) who use cannabis compared to non-users (17.2 versus 12.5%). 28 A recent systematic review and meta-analysis also noted an increase in NICU admission among neonates exposed to cannabis in utero (pooled OR 2.02, 95% CI 1.27–3.21). 6 The observed increased risk of NICU admission in these and other studies 29 , coupled with our finding of increased neonatal morbidity, emphasizes the need to rigorously evaluate neonatal morbidity in this population.…”
Section: Commentmentioning
confidence: 96%
“…In a retrospective records study, maternal use of cannabis, as determined by either self-report or a positive urine assay for THC, was associated with decrements in fetal growth (e.g. small-for-gestational age) and an increase of 54% in neonatal intensive care unit admissions (Warshak et al, 2015). This investigation is particularly noteworthy as women who used tobacco during pregnancy were not included in the study population.…”
Section: Impact Of Prenatal Cannabis Exposure On Neurodevelopmental Omentioning
confidence: 99%